Zapojení mikroRNA do patogeneze nádorových onemocnení a moznosti jejich vyuzití v diagnostické a prediktivní onkologii - Slabý, O; Krekác, D; Hrstka, R; Svoboda, M; Vyzula, R (Casopis lekaru ceskych, 2008)
MicroRNAs (miRNAs) are large class of non-coding RNAs that post-transcriptionally regulate gene expression. Their ability of translational repression applied for example on oncogenes or tumor-suppressor genes indicates involvement of miRNAs in multi-step carcinogenesis. Evidences of miRNAs linkage to biological processes like apoptosis, proliferation, differentiation and cell survival are rapidly accumulating. Approximately 50% of miRNAs are located at fragile sites of chromosomes or regions known to be amplified or deleted in human cancer. That is why, non-coding miRNAs seem to be another level of genetic information which regulation is altered or lost during neoplastic growth. Expression profiles of miRNAs are successfully used for molecular classification, more exact diagnosis and prognosis of human cancers and reached analogical analytical characteristics like studies based on DNA micro-arrays technology and profiling of coding transcripts. In this review we attempt to introduce basic knowledge of miRNAs biogenesis and biological functions and in particular summarise reports focused on miRNAs in oncology research area.
Keywords: Neoplasms; MicroRNAs; lidé; Humans; mikro RNA; nádory